2019
DOI: 10.1186/s12950-019-0212-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of autophagy in atherosclerosis: foe or friend?

Abstract: Athrosclerosis is conceived as a chronic inflammatory status affecting cells from vascular walls. Different mechanisms and pathological features are evident at the onset of atherosclerotic changes via the engaging different cells from the vascular wall and circulatory cells. Attempts are currently focused on the detection of cell compensatory mechanisms against atherosclerotic changes to restore cell function and/or postpone severe vasculitis. Autophagy is an intracellular self-digesting process commonly protr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 80 publications
0
68
0
Order By: Relevance
“…In these reports, the relationship with autophagy is unknown. To date, many preclinical studies on the relationship between autophagy and cardiovascular diseases have been performed [62,63]. From those studies, it has been suggested that autophagy plays a dual role in cardiovascular disease progression, acting in either beneficial or maladaptive ways, depending on the context.…”
Section: Discussionmentioning
confidence: 99%
“…In these reports, the relationship with autophagy is unknown. To date, many preclinical studies on the relationship between autophagy and cardiovascular diseases have been performed [62,63]. From those studies, it has been suggested that autophagy plays a dual role in cardiovascular disease progression, acting in either beneficial or maladaptive ways, depending on the context.…”
Section: Discussionmentioning
confidence: 99%
“…The most important factor underlying atherosclerosis is abnormal lipid metabolism, especially hypercholesterolemia, for which low-density lipoprotein cholesterol (LDL-C) is an acknowledged risk factor. LDL-C enters the vascular intima through damaged endothelial cells and is converted to oxidized low-density lipoprotein cholesterol (ox LDL-C), which can be recognized by the scavenger receptor (SR) of vascular smooth muscle cells (VSMCs) and monocyte-derived macrophages and then engulfed to form foam cells and early lipid streaks [10] (Figure 1). TRPV1 can regulate lipid metabolism, initially by reducing blood lipid levels, and Ma et al, who fed capsaicin to atherosclerotic mice, showed that compared with those in ApoE (−/−) TRPV1 (−/−) mice, the serum total cholesterol and triglyceride levels in apolipoprotein E knockout mice (ApoE (−/−) ) mice were significantly reduced, and lipid accumulation in aortic SMCs was also significantly reduced [11].…”
Section: Regulation Of Lipid Metabolismmentioning
confidence: 99%
“…Atherosclerosis is considered to be a chronic inflammatory disease that mainly refers to large myoelastic arteries (e.g., the aorta) and mediumsized myoelastic arteries (e.g., coronary and cerebral arteries) [8].The risk factors for atherosclerosis include hypertension, hyperlipidemia, diabetes, obesity and smoking [9]. The pathogenesis mainly includes endothelial cell injury, lipid deposition, foam cell formation, inflammation, oxidative stress, and SMCs proliferation, among others [10] ( Figure 1).…”
Section: Introduction Of Atherosclerosismentioning
confidence: 99%
“…Autophagy has dual effects on AS, a chronic inflammatory disease. Although autophagy can prevent early changes associated with AS by inhibiting inflammatory cells and maintaining the stability of vascular wall cells, it can also aggravate the disease in late AS stage [30].…”
mentioning
confidence: 99%